The impact of prenatal use of oral Clostridium butyricum on maternal group B Streptococcus colonization: A retrospective study - Ting-Jung Lai; Ya-Hui Wang; Eva Chong; Ying-Mei Lin; Chao-Chi Huang; Kuan-Jen Feng; Sen-Wen Teng (Elsevier, 2021)
Objective: The aim of this study is to examine the effect of taking Clostridium butyricum (Miyarisan BM) orally for 4 weeks since the 32+0 weeks of gestation on preventing Group B Streptococcus colonization. Materials and methods: We retrospectively collected data on the pregnancy outcomes of 1602 women between October 2017 and August 2019. The control group received standard antenatal care, and the intervention group received standard antenatal care with a daily oral dose of probiotics since the 32+0 weeks of gestation. The daily dose was one pack of C. butyricum (Miyarisan BM) once or twice a day. A vaginal Group B Streptococcus swab was collected between 36+0 and 36+6 weeks of gestation. Results: After applying the designated exclusion criteria, the total number of participants was 1576. The Group B Streptococcus colonization rate was significantly decreased in the intervention group (P = 0.0338; adjusted OR: 0.66 (0.45-0.97)). Conclusion: Probiotics can reduce the colonization rate of Group B Streptococcus in the vagina and rectum under three conditions: (1) intervention of adequate length, (2) sufficient probiotic dose, and (3) effective probiotics.